Combined family-based association and linkage analyses in families affected by attention-deficit hyperactivity disorder - Cristina M. Justice; Kwangmi Ahn; Benjamin Jung; Luke J. Norman; Gustavo Sudre; Wendy Sharp; Marine Bouyssi-Kobar; Saadia Choudhury; Stevi Gligorovic; Paul Kundzicz; Maria T. Acosta; Philip Shaw (Human Genetics, 2026)
Attention deficit hyperactivity disorder (ADHD) is one of the most prevalent and heritable of neurodevelopmental disorders. To characterize the genetic variants contributing to this heritability, we studied families with members affected by ADHD. Genome-wide array data were obtained on two cohorts: NHGRI Family Cohort (359 nuclear families,1538 individuals) and NCR Family Cohort (25 multigenerational and 132 nuclear families, 631 members). A meta-analysis of family-based association tests (FBAT) of the two cohorts identified three genome-wide significant associations, one upstream from TFRC , and two that were intronic to GSDME and to TRIM31 , with the last gene previously implicated in ADHD. Genes associated with ADHD (MAGMA, gene-based association P < 0.05) overlapped with genes implicated in ADHD by prior case/control genome-wide association studies. Meta-analyses of the linkage signals identified one significant linkage region (LOD > 3) on 19p13.2-13.11 that encompassed a genome-wide significant variant in the FBAT of the NHGRI Family Cohort (rs55741253, P = 2.68 × 10 − 8 ). Additionally, two of the five linkage regions that reached a LOD > 2 in our meta-analysis replicated significant linkages from prior studies (prior studies reporting 13 linkages with LOD > 3.0; hypergeometric test of overlapping linkage signals, P < 0.01). Using neuroimaging data from the NCR cohort, we found genes associated with ADHD overlapped with genes associated with the brain’s total surface area and a feature of functional connectivity, reflecting the interaction between the brain’s default mode and task positive networks. Such work begins to delineate the neural substrates of the discovered genetic associations with familial ADHD.

Micronization of wholewheat flour increases iron bioavailability from hydrothermally processed wheat flour dough - Mohamad F. Aslam; Sarah M. Arafsha; Sarah E. Berry; Balazs Bajka; Peter R. Ellis; Gladys O. Latunde-Dada; Paul A. Sharp (Food Research International, 2024)

A quantitative classification method of land uses and assessment of per-and poly-fluoroalkyl substances (PFAS) occurrence in freshwater environments - Paula Sardiña; Simon Sharp; Minna Saaristo; Timothy Coggan; Molly Hoak; Paul Leahy (Environmental Pollution, 2024)

Elemental characterization of electronic waste: a review of research methodologies and applicability to the practice of e-waste recycling - Amarachukwu Agbim; Kelsea A. Schumacher; Nicholas Sharp; Rick Paul; Ruthmara Corzo (Waste Management, 2024)

Correction: Long-chain omega-3 polyunsaturated fatty acids decrease mammary tumor growth, multiorgan metastasis and enhance survival - Saraswoti Khadge; Geoffrey M. Thiele; John Graham Sharp; Timothy R. McGuire; Lynell W. Klassen; Paul N. Black; Concetta C. DiRusso; Leah Cook; James E. Talmadge (Clinical & Experimental Metastasis, 2023)

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Best Practice Data Standards for Discrete Chemical Oceanographic Observations - Li-Qing Jiang; Denis Pierrot; Rik Wanninkhof; Richard A. Feely; Bronte Tilbrook; Simone Alin; Leticia Barbero; Robert H. Byrne; Brendan R. Carter; Andrew G. Dickson; Jean-Pierre Gattuso; Dana Greeley; et al. (Frontiers in Marine Science, 2022)
Effective data management plays a key role in oceanographic research as cruise-based data, collected from different laboratories and expeditions, are commonly compiled to investigate regional to global oceanographic processes. Here we describe new and updated best practice data standards for discrete chemical oceanographic observations, specifically those dealing with column header abbreviations, quality control flags, missing value indicators, and standardized calculation of certain properties. These data standards have been developed with the goals of improving the current practices of the scientific community and promoting their international usage. These guidelines are intended to standardize data files for data sharing and submission into permanent archives. They will facilitate future quality control and synthesis efforts and lead to better data interpretation. In turn, this will promote research in ocean biogeochemistry, such as studies of carbon cycling and ocean acidification, on regional to global scales. These best practice standards are not mandatory. Agencies, institutes, universities, or research vessels can continue using different data standards if it is important for them to maintain historical consistency. However, it is hoped that they will be adopted as widely as possible to facilitate consistency and to achieve the goals stated above.

Provenance and genetic diversity of the non-native geckos Phelsuma grandis Gray 1870 and Gekko gecko (Linnaeus 1758) in southern Florida, USA - Thomas W. Fieldsend; Kenneth L. Krysko; Paul Sharp; Timothy M. Collins (Biological Invasions, 2021)

Toward a global and reproducible science for brain imaging in neurotrauma: the ENIGMA adult moderate/severe traumatic brain injury working group - Alexander Olsen; Talin Babikian; Erin D. Bigler; Karen Caeyenberghs; Virginia Conde; Kristen Dams-O’Connor; Ekaterina Dobryakova; Helen Genova; Jordan Grafman; Asta K. Håberg; Ingrid Heggland; Torgeir Hellstrøm; et al. (Brain Imaging and Behavior, 2021)
The global burden of mortality and morbidity caused by traumatic brain injury (TBI) is significant, and the heterogeneity of TBI patients and the relatively small sample sizes of most current neuroimaging studies is a major challenge for scientific advances and clinical translation. The ENIGMA (Enhancing NeuroImaging Genetics through Meta-Analysis) Adult moderate/severe TBI (AMS-TBI) working group aims to be a driving force for new discoveries in AMS-TBI by providing researchers world-wide with an effective framework and platform for large-scale cross-border collaboration and data sharing. Based on the principles of transparency, rigor, reproducibility and collaboration, we will facilitate the development and dissemination of multiscale and big data analysis pipelines for harmonized analyses in AMS-TBI using structural and functional neuroimaging in combination with non-imaging biomarkers, genetics, as well as clinical and behavioral measures. Ultimately, we will offer investigators an unprecedented opportunity to test important hypotheses about recovery and morbidity in AMS-TBI by taking advantage of our robust methods for large-scale neuroimaging data analysis. In this consensus statement we outline the working group’s short-term, intermediate, and long-term goals.

Dissolution and Translational Modeling Strategies Toward Establishing an In Vitro-In Vivo Link—a Workshop Summary Report - Tycho Heimbach; Sandra Suarez-Sharp; Maziar Kakhi; Nico Holmstock; Andrés Olivares-Morales; Xavier Pepin; Erik Sjögren; Eleftheria Tsakalozou; Paul Seo; Min Li; Xinyuan Zhang; Ho-Pi Lin; et al. (The AAPS Journal, 2019)

Long-chain omega-3 polyunsaturated fatty acids decrease mammary tumor growth, multiorgan metastasis and enhance survival - Saraswoti Khadge; Geoffrey M. Thiele; John Graham Sharp; Timothy R. McGuire; Lynell W. Klassen; Paul N. Black; Concetta C. DiRusso; Leah Cook; James E. Talmadge (Clinical & Experimental Metastasis, 2018)

Applications of Clinically Relevant Dissolution Testing: Workshop Summary Report - Sandra Suarez-Sharp; Michael Cohen; Filippos Kesisoglou; Andreas Abend; Patrick Marroum; Poonam Delvadia; Evangelos Kotzagiorgis; Min Li; Anna Nordmark; Nagesh Bandi; Erik Sjögren; Andrew Babiskin; et al. (The AAPS Journal, 2018)

Assessing uncertainties in crop and pasture ensemble model simulations of productivity and N 2 O emissions - Fiona Ehrhardt; Jean‐François Soussana; Gianni Bellocchi; Peter Grace; Russel McAuliffe; Sylvie Recous; Renáta Sándor; Pete Smith; Val Snow; Massimiliano de Antoni Migliorati; Bruno Basso; Arti Bhatia; et al. (Global Change Biology, 2018)
Simulation models are extensively used to predict agricultural productivity and greenhouse gas emissions. However, the uncertainties of (reduced) model ensemble simulations have not been assessed systematically for variables affecting food security and climate change mitigation, within multi‐species agricultural contexts. We report an international model comparison and benchmarking exercise, showing the potential of multi‐model ensembles to predict productivity and nitrous oxide (N 2 O) emissions for wheat, maize, rice and temperate grasslands. Using a multi‐stage modelling protocol, from blind simulations (stage 1) to partial (stages 2–4) and full calibration (stage 5), 24 process‐based biogeochemical models were assessed individually or as an ensemble against long‐term experimental data from four temperate grassland and five arable crop rotation sites spanning four continents. Comparisons were performed by reference to the experimental uncertainties of observed yields and N 2 O emissions. Results showed that across sites and crop/grassland types, 23%–40% of the uncalibrated individual models were within two standard deviations ( SD ) of observed yields, while 42 (rice) to 96% (grasslands) of the models were within 1 SD of observed N 2 O emissions. At stage 1, ensembles formed by the three lowest prediction model errors predicted both yields and N 2 O emissions within experimental uncertainties for 44% and 33% of the crop and grassland growth cycles, respectively. Partial model calibration (stages 2–4) markedly reduced prediction errors of the full model ensemble E‐median for crop grain yields (from 36% at stage 1 down to 4% on average) and grassland productivity (from 44% to 27%) and to a lesser and more variable extent for N 2 O emissions. Yield‐scaled N 2 O emissions (N 2 O emissions divided by crop yields) were ranked accurately by three‐model ensembles across crop species and field sites. The potential of using process‐based model ensembles to predict jointly productivity and N 2 O emissions at field scale is discussed.

Regulatory Experience with In Vivo In Vitro Correlations (IVIVC) in New Drug Applications - Sandra Suarez-Sharp; Min Li; John Duan; Heta Shah; Paul Seo (The AAPS Journal, 2016)

Regulatory Perspectives on Strength-Dependent Dissolution Profiles and Biowaiver Approaches for Immediate Release (IR) Oral Tablets in New Drug Applications - Sandra Suarez-Sharp; Poonam R. Delvadia; Angelica Dorantes; John Duan; Anna Externbrink; Zongming Gao; Tapash Ghosh; Sarah Pope Miksinski; Paul Seo (The AAPS Journal, 2016)

Physiological Employment Standards III: physiological challenges and consequences encountered during international military deployments - Bradley C. Nindl; John W. Castellani; Bradley J. Warr; Marilyn A. Sharp; Paul C. Henning; Barry A. Spiering; Dennis E. Scofield (European Journal of Applied Physiology, 2013)

CDER Risk Assessment Exercise to Evaluate Potential Risks from the Use of Nanomaterials in Drug Products - Celia N. Cruz; Katherine M. Tyner; Lydia Velazquez; Kenneth C. Hyams; Abigail Jacobs; Arthur B. Shaw; Wenlei Jiang; Robert Lionberger; Peter Hinderling; Yoon Kong; Paul C. Brown; Tapash Ghosh; et al. (The AAPS Journal, 2013)

Correlations Between Gene Expression and Mercury Levels in Blood of Boys With and Without Autism - Boryana Stamova; Peter G. Green; Yingfang Tian; Irva Hertz-Picciotto; Isaac N. Pessah; Robin Hansen; Xiaowei Yang; Jennifer Teng; Jeffrey P. Gregg; Paul Ashwood; Judy Van de Water; Frank R. Sharp (Neurotoxicity Research, 2011)

Correlations of Gene Expression with Blood Lead Levels in Children with Autism Compared to Typically Developing Controls - Yingfang Tian; Peter G. Green; Boryana Stamova; Irva Hertz-Picciotto; Isaac N. Pessah; Robin Hansen; Xiaowei Yang; Jeffrey P. Gregg; Paul Ashwood; Glen Jickling; Judy Van de Water; Frank R. Sharp (Neurotoxicity Research, 2011)

Increasing CNS Noradrenaline Reduces EAE Severity - Maria Vittoria Simonini; Paul E. Polak; Anthony Sharp; Susan McGuire; Elena Galea; Douglas L. Feinstein (Journal of Neuroimmune Pharmacology, 2010)

A novel approach identified the FOLR1 gene, a putative regulator of milk protein synthesis - Karensa K. Menzies; Christophe Lefèvre; Julie A. Sharp; Keith L. Macmillan; Paul A. Sheehy; Kevin R. Nicholas (Mammalian Genome, 2009)

Pleistocene climatic cycling and diversification of the Andean treefrog, Hypsiboas andinus - DARIA KOSCINSKI; PAUL HANDFORD; PABLO L. TUBARO; SARAH SHARP; STEPHEN C. LOUGHEED (Molecular Ecology, 2008)
Our understanding of the causes of diversification of Neotropical organisms lags behind that of Northern Hemisphere biota, especially for montane and temperate regions of southern South America. We investigated the mitochondrial DNA genealogical patterns in 262 individuals of the frog Hypsiboas andinus from 26 sites across the eastern ranges of the Andes Mountains in Argentina and Bolivia. Our phylogenetic analyses indicate at least three distinct lineages: one representing H. andinus from Northwestern Argentina and southern Bolivia, at least one H. andinus lineage from northern Bolivia, and one clade containing both H. andinus (from the southern portion of the species range) and its putative sister taxon Hypsiboas riojanus . Hypsiboas andinus samples from northern Bolivia are well differentiated and may represent distinct species. The northern Argentine H. andinus lineage and southern H. andinus / H. riojanus lineage likely diverged between 2 and 6 million years ago; their current sympatry may be the result of secondary contact due to range expansion after isolation during Andean uplift or may reflect cryptic species. Within the geographically extensive northern H. andinus clade, we found significant geographical structuring consistent with historical fragmentation and subsequent range expansion. The timing of this fragmentation and range expansion coincide with the Pleistocene, a time of extensive climatic cycling and vegetational shifts. Average divergence among clades is lower than those found for other Neotropical taxa, highlighting the potential importance of recent climatic history in diversification in the southern Andes.

The Environmental Polymorphisms Registry: a DNA resource to study genetic susceptibility loci - Patricia C. Chulada; Heather L. Vahdat; Richard R. Sharp; Tracy C. DeLozier; Paul B. Watkins; Susan N. Pusek; Perry J. Blackshear (Human Genetics, 2008)

A microbiological survey of Montserrat Island hydrothermal biotopes - Tony Atkinson; Steven Cairns; D. A. Cowan; Michael J. Danson; David W. Hough; D. Barrie Johnson; Paul R. Norris; Neil Raven; Clare Robinson; Rob Robson; Richard J. Sharp (Extremophiles, 2000)